Розкопки на Циркунівському городищі скіфського часу у 2009 р. - Пеляшенко, К.Ю. (Археологічні дослідження в Україні, 2010)
Results of the 2009 excavations at the Scythian period hillfort Tsyrkuny are briefly described. The work concentrated at two areas: at the defensive structures and hill-fort area on the territory of «the Third yard» (9 and 9a excavation areas), and at the burnt mound on the territory of «the Second yard» (10 excavation area). The results obtained enlarge the data on fortifications, continuity and the nature of the hill-fort settling.